Answer:
-2 and 26
Step-by-step explanation:
Multiply to -52:
-2 * 26= -52
Add to 24
-2+26= 24
Answer:
All Real
Step-by-step explanation:
Answer:
![y = - 3x + 27](https://tex.z-dn.net/?f=y%20%3D%20%20-%203x%20%2B%2027)
Step-by-step explanation:
The standard form for the equation of the line is
![y = mx + c](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20c)
Recall that:
![y = 0 \: \: \: x = 9 \: \: \: m = - 3 \\ y = mx + c \\ 0 = - 3(9) + c \\ 0 = - 27+ c \\ 27 = c](https://tex.z-dn.net/?f=y%20%3D%200%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20x%20%3D%209%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20m%20%3D%20%20-%203%20%5C%5C%20y%20%3D%20mx%20%2B%20c%20%5C%5C%200%20%3D%20%20-%203%289%29%20%2B%20c%20%5C%5C%200%20%3D%20%20-%2027%2B%20c%20%5C%5C%2027%20%3D%20c)
Therefore the equation of the line is:
![y = mx + c \\ y = - 3x + 27](https://tex.z-dn.net/?f=y%20%3D%20mx%20%2B%20c%20%5C%5C%20y%20%3D%20%20-%203x%20%2B%2027)